2010
DOI: 10.1523/jneurosci.1376-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cortical Plasticity Underlying Novel Word Learning

Abstract: Humans are unique in developing large lexicons as their communication tool. To achieve this, they are able to learn new words rapidly. However, neural bases of this rapid learning, which may be an expression of a more general cognitive mechanism, are not yet understood. To address this, we exposed our subjects to familiar words and novel spoken stimuli in a short passive perceptual learning session and compared automatic brain responses to these items throughout the learning exposure. Initially, we found enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 20 publications
15
119
3
2
Order By: Relevance
“…In contrast, the activation seen in the present study for novel word forms with both native and non-native phonology indicates response enhancement which not only counteracts but overrides any repetition-related suppression. Although not directly comparable, these results tentatively support previous findings in adults (e.g., Shtyrov et al, 2010;Yue, Bastiaanse, & Alter, 2014;Kimppa et al, 2015Kimppa et al, , 2016: similarly to the findings with adults, we observed an increase of activation to novel word forms in the left temporal region, which may be indicative of adults and children utilising at least partially similar networks for rapid formation of memory traces for novel word forms. As previous studies indicate that the language lateralisation is fully established by the age of 5 years (or earlier), with only minimal changes later in development (Weiss-Croft & Baldeweg, 2015), this response enhancement in the left temporal region is highly indicative of reliance on a neural network tuned for native language processing.…”
Section: Neural Dynamics and Substrate Of Online Memory-trace Build-usupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the activation seen in the present study for novel word forms with both native and non-native phonology indicates response enhancement which not only counteracts but overrides any repetition-related suppression. Although not directly comparable, these results tentatively support previous findings in adults (e.g., Shtyrov et al, 2010;Yue, Bastiaanse, & Alter, 2014;Kimppa et al, 2015Kimppa et al, , 2016: similarly to the findings with adults, we observed an increase of activation to novel word forms in the left temporal region, which may be indicative of adults and children utilising at least partially similar networks for rapid formation of memory traces for novel word forms. As previous studies indicate that the language lateralisation is fully established by the age of 5 years (or earlier), with only minimal changes later in development (Weiss-Croft & Baldeweg, 2015), this response enhancement in the left temporal region is highly indicative of reliance on a neural network tuned for native language processing.…”
Section: Neural Dynamics and Substrate Of Online Memory-trace Build-usupporting
confidence: 90%
“…On the basis of visual inspection, three peaks were identified: 91, 317, and 452 ms from stimulus onset. As in previous studies (Shtyrov et al, 2010, Yue, Bastiaanse & Alter, 2014Kimppa et al, 2015) showing rapid lexical acquisition effects at latencies around ~50-120 ms, we a priori focussed on the first two peaks as they fall fell within 200 ms after the disambiguation points (see Figure 1, and the Stimuli section above). Ad hoc, we also analysed the peak at 452ms as well to verify that no similar effects were present at a later stage.…”
Section: Meg Recording and Data Analysismentioning
confidence: 99%
“…Although many studies have found that one-time acquisition occurs during word learning (Borovsky et al, 2010(Borovsky et al, , 2012Shtyrov, 2011;Shtyrov, Nikulin, & Pulvermüller, 2010), more evidence suggests that we still need practice and repetition to consolidate and refine word learning (Medina et al, 2011;Mestres-Missé et al, 2007Munro, Baker, McGregor, Docking, & Arciuli, 2012;Ramscar et al, 2013). Studies on children's word learning found that repetition of context (stories or non-target words) is better in facilitating word learning than an equal number of varied contexts (Axelsson & Horst, 2014;Williams & Horst, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Saffran, Newport, Aslin, Tunick, and Barrueco (1997) found young adults and first-grade children to be equally skilled at segmenting and storing novel words from a string of nonsense syllables in an incidental learning task. More recently, Shtyrov, Nikulin, and Pulvermüller (2010) reported a neurophysiological counterpart of these behavioural findings on the early stages of word learning. After as little as 14 min of passive listening, neural response patterns to novel words became qualitatively identical to those elicited by existing words, suggesting that memories of the novel words had been established.…”
Section: Introductionmentioning
confidence: 87%